(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
This study focuses on the training of future pedagogy specialists for the effective implementation of the normatively defined general and additional support for children and students with chronic diseases. This is also the author’s starting position for an analysis of the main legislative documents that define the framework for active pedagogical activities, required for the inclusion of children and students at risk of social exclusion from the education system. The additional subject of the study is to outline the requirement to introduce academic disciplines aimed at forming competencies for working with children and students with chronic diseases as part of the training of students from the Faculty of Pedagogy at the Trakia University of Stara Zagora. The hypothesis of the study is that in the process of forming prosocial behavior in children and students, especially towards their peers with chronic diseases, pedagogical specialists can greatly benefit from the support of relevant information materials adapted for different age groups.